POSHAN's abstract digest on maternal and child nutrition research - Issue 27 - Avula, Rasmi (International Food Policy Research Institute, 2019)
We are delighted to present another issue of Abstract Digest with a collection of interesting and insightful articles on various aspects of maternal and child nutrition, from around the world, with relevance to India. Four articles in this issue used different rounds of the National Family Health Survey data to examine a range of issues including trends in mortality rates, developing an algorithm for predicting newborns’ risk of undernutrition in the first 5 years of life, estimating burden of malnutrition, and coverage and equity of Integrated Child Development Services program.